2017
DOI: 10.1080/21691401.2017.1332635
|View full text |Cite|
|
Sign up to set email alerts
|

Green synthesis of magnetic Fe3O4 nanoparticles using Couroupita guianensis Aubl. fruit extract for their antibacterial and cytotoxicity activities

Abstract: In the present study, a sustainable green chemistry approach was established to fabricate magnetic FeO nanoparticles (FeONPs) using the aqueous fruit extract of edible C. guianensis (CGFE). Synthesized NPs were further confirmed with different high-throughput characterization techniques such as UV-visible spectroscopy, FT-IR, XPS, DLS and zeta potential analysis. Additionally, XRD, AFM, HRTEM and SQUID VSM demonstrate the generation of crystalline CGFeONPs with mean diameter of 17 ± 10 nm. Interestingly, CGFeO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
44
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(61 citation statements)
references
References 50 publications
(50 reference statements)
8
44
0
Order By: Relevance
“…Various dimensions of images ( Figure 5(a-f)) were utilized to detect clearly NPs. As illustrated in Figure 5 showed size distribution range 7-77 nm for green synthesized magnetic Fe 3 O 4 NPs by fruit extract of Couroupita guianensis Aubl [62]. Therefore, as a comparative approach, our results showed reduction and uniformity of Fe 3 O 4 NPs size.…”
Section: Sem Images Edax and Afm Analysismentioning
confidence: 51%
See 2 more Smart Citations
“…Various dimensions of images ( Figure 5(a-f)) were utilized to detect clearly NPs. As illustrated in Figure 5 showed size distribution range 7-77 nm for green synthesized magnetic Fe 3 O 4 NPs by fruit extract of Couroupita guianensis Aubl [62]. Therefore, as a comparative approach, our results showed reduction and uniformity of Fe 3 O 4 NPs size.…”
Section: Sem Images Edax and Afm Analysismentioning
confidence: 51%
“…As illustrated in Figure 5(d), lower height of 2.73 nm and uniformity of size distribution were observed for Fe 3 O 4 NPs. In this case, the previous study showed size distribution range 7-77 nm for green synthesized magnetic Fe 3 O 4 NPs by fruit extract of Couroupita guianensis Aubl [62].…”
Section: Spreading Assay Of Staphylococcus Aureusmentioning
confidence: 68%
See 1 more Smart Citation
“…Further, CGFE and CGFe 3 O 4 NPs treated HepG2 cells showed modified features like condensed nuclei, apoptotic bodies of nuclear morphology and membrane blebbing. These results made the authors to strongly suggest that CGFe 3 O 4 NPs induces HepG2 cell death through caspase-cascade mediated mitochondrial dysfunction and apoptosis (66). A similar MTT assay was carried out by the same author with palladium nanoparticles (CGPdNPs) obtained from CG fruit extract (CGFE) on lung cancer cell line A549.…”
Section: Anticytotoxic Activitymentioning
confidence: 78%
“…In addition to all this biosynthesized NPs are usually biocompatible and highly applicable for biomedical applications [16,17,18]. Green synthesis of different NPs by plants such as Acalypha indica, Rosa hybrid, Marraya koenigii, Tanacetum vulgar, Punica granatum, Tamarindus indica, Prunus japonica, Couroupita guianensis, Borago officinalis, etc., has been reported [23][24][25][26][27][28]. This begs a question; whether the use of naturally occurring phytochemicals pose any strategic advantage over using chemically purified counterparts, other than just being cheaper or naturally available?…”
Section: Introductionmentioning
confidence: 99%